2016
DOI: 10.18240/ijo.2016.05.18
|View full text |Cite
|
Sign up to set email alerts
|

Ocular trauma treated with pars plana vitrectomy: early outcome report

Abstract: Trauma is more likely to occur in men under 40y of age and in the workplace. The favorable final visual outcome is associated with the absence of afferent pupillary defect, ocular trauma score and presenting visual acuity as well as the zone of injury, and not associated with the timing of vitrectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…A study led by Mansouri et al . showed that the timing of vitrectomy was not associated with the visual outcome among 90 patients with ocular injuries involving the posterior segment 18 . Similarly, Ghoraba et al .…”
Section: Discussionmentioning
confidence: 97%
“…A study led by Mansouri et al . showed that the timing of vitrectomy was not associated with the visual outcome among 90 patients with ocular injuries involving the posterior segment 18 . Similarly, Ghoraba et al .…”
Section: Discussionmentioning
confidence: 97%
“…All data were anonymized and de-identified before analysis. Indications for vitrectomy following ocular trauma included [ 1 ] intraocular foreign bodies, [ 2 ] suspected posterior capsule rupture, [ 3 ] dense vitreous hemorrhage with b scan suspicious for retinal detachment, [ 4 ] zone 2/3 injuries (zone 1 may also have been involved), and/or [ 5 ] endophthalmitis. All vitrectomies were performed using the 23 g Constellation system (Alcon Laboratories Inc, USA).…”
Section: Methodsmentioning
confidence: 99%
“…It is estimated that there are around 2.0 million cases of eye trauma that occur each year in the United States, with approximately 1 million individuals having permanent visual impairment because of injury [ 1 ]. Pars plana vitrectomy (PPV) has played a major role in improving outcomes of ocular trauma by allowing posterior segment reconstruction, clearing vitreous opacities, and preventing endophthalmitis [ 2 ]. However, the optimum timing of PPV has been a topic of on-going debate [ 3 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…1 Pars plana vitrectomy (PPV) has played a major role in improving the outcomes of ocular trauma with reconstruction of the posterior segment, clearance of vitreous opacities, and prevention of endophthalmitis. 2 The use of oral prednisone in the perioperative period after globe repair is controversial and has been proposed as a meas ure to reduce the incidence of postsurgical inflammation and proliferative vitreoretinopathy (PVR). The role of adjuvant therapies such as oral prednisone remains a topic of debate.…”
Section: Introductionmentioning
confidence: 99%